ОБРАЗ УКРАЇНИ В КОЗАЦЬКО-СТАРШИНСЬКИХ ЛІТОПИСАХ (Zaporizhzhia Historical Review, 2021)
In this article the questions of cossacks expanse thoughts about Ukraine are analyzed, the origin of the name «Ukraine» is investigated. The article is based on the text’s analysis of the cossacks chronicles: Samovidzcha, G.Grabyanki, S.Velichka. The author came to the conclusion that perception of Ukraine by cozakdom is changed greatly during the 2nd part of XVII – 1st part of XVIII centuries, but those changes hadn’t chaotic character, but they were the part of common European process of organization of nations.